Analisa Laporan Penyelenggaraan Pemerintah Daerah di Masa Pandemi Covid-19 - Virdanti, Citra Ramadhani Ayu Nur; Triputro, R. Widodo (Jurnal Administrasi Pemerintahan Desa, 2022)
The preparation of the LPPD is a form of accountability for the administration of local government in Sleman Regency for one year. This is mandatory because it has been stated in Law Number 23 of 2014 concerning Regional Government. In addition, the results of the collection of LPPDs to the Central Government will be used as a reference for policy-making on regional problems as well as an early detection tool for national policy problems.